Islam: Local and Global Challenges - Editor Al-Jami'ah: Journal of Islamic Studies (Al-Jami'ah Research Centre, 2011)
Indeed, in maintaining their local values when faced with global challenges, Muslims, as a social entity, and Islam, as a set of dogma, have given birth to new phenomena, e.g. new interpretation of Islam within a new context. Additionally, this era of globalization has led religions, including Islam, to renew their gambit to cope reality, e.g. in the practical life (sociological, political, economical and anthropological aspects), intellectual endeavors (philosophical and theological aspects), and in the renewal of dogmatic teachings (hermeneutical aspects).